Corporate governance : promises kept, promises broken - Macey, Jonathan R. (Princeton University Press, 2008)
Even in the wake of the biggest financial crash of the postwar era, the United States continues to rely on Securities and Exchange Commission oversight and the Sarbanes-Oxley Act, which set tougher rules for boards, management, and public accounting firms to protect the interests of shareholders. Such reliance is badly misplaced. In Corporate Governance, Jonathan Macey argues that less government regulation--not more--is what's needed to ensure that managers of public companies keep their promises to investors. Macey tells how heightened government oversight has put a stranglehold on what is t.